НЕКОТОРЫЕ ИСТОРИЧЕСКИЕ АСПЕКТЫ ИЗУЧЕНИЯ ЭТАПОВ РАЗВИТИЯ ОСНОВНЫХ ЭКОЛОГИЧЕСКИХ ПРОБЛЕМ ЮЖНОГО ПРИАРАЛЬЯ - Кайпназаров, А.Ш. (SCIENCE and SOCIETY, 2020)
The article discusses the history of the development of the main environmental problems in the South Aral Sea region. An incorrect development strategy for the productive forces of the region is indicated as the main reason for the development of this phenomenon. It is emphasized that, given the extensive experience in solving environmental problems, measures are being taken to preserve the environment.